ANALISIS EFISIENSI BOILER TERHADAP POLA PENGOPERASIAN SOOTBLOWER DI PLTU SURALAYA - Yudhi Chandra Dwiaji; Didik Margi Utama (JURNAL SIMETRIK, 2020)
Perusahaan Listrik Negara (Persero) PT announced electricity consumption in the first half of 2018 was 112.46 TeraWatt hour (TWh) or grew 4.7 percent on an annual basis. With the continued increase in electricity demand, electricity providers are required to be able to provide reliable, stable and efficient electricity production to the public. High efficiency in an electricity production in a power plant can be seen from the performance or efficiency of the boiler, because the power of a boiler is the same as the power of a power plant. The boiler efficiency is obtained from calculating the ratio between the output energy and the boiler input energy. Boiler efficiency is influenced by the cleanliness of the boiler from coal ash deposits. Cleaning can be done by operating the sootblower. The sootblower operation method will affect the value of boiler efficiency which gives an idea of how much efficiency the boiler  when the boiler is operating. As based on the analysis of the calculations that have been made, the results of the boiler efficiency decrease when the sootblower is operating. The highest decrease in boiler efficiency during the sootblower process is 2.22%, the lowest decrease in boiler efficiency during the process is 1.08% and the average decrease during the sootblower process is 1.73%. While the impact of sootblower operation, boiler efficiency has decreased 11 times and has increased 8 times, indicating that the sootblower operating method in PLTU Suralaya is not effective.